Regulation of IFN‐γ by IL‐13 dictates susceptibility to secondary postinfluenza MRSA pneumonia. Issue 11 (1st September 2014) - Rynda‐Apple, Agnieszka; Harmsen, Ann; Erickson, Anfin S.; Larson, Kyle; Morton, Rachelle V.; Richert, Laura E.; Harmsen, Allen G.
<x xml:space="preserve">Abstract</x> Superinfection in mice at day 7 postinfluenza infection exacerbates bacterial pneumonia at least in part via downstream effects of increased IFN‐γ signaling. Here we show that up to 3 days postinfluenza infection, mice have reduced susceptibility to superinfection with methicillin‐resistant Staphylococcus aureus (MRSA), but that superinfection during that time exacerbated influenza disease. This was due to IL‐13 signaling that was advantageous for resolving MRSA infection via inhibition of IFN‐γ, but was detrimental to the clearance of influenza virus. However, if superinfection did not occur until the near resolution of influenza infection (day 7), IL‐13 signaling was inhibited, at least in part by upregulation of IL‐13 decoy receptor (IL‐13Rα2), which in turn caused increases in IFN‐γ signaling and exacerbation of bacterial infection. Understanding these cytokine sequelae is critical to development of immunotherapies for influenza‐MRSA coinfection since perturbations of these sequelae at the wrong time could increase susceptibility to MRSA and/or influenza.